2014
DOI: 10.1152/jn.00419.2013
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a reference frame transformation of vestibular signal contributions to voluntary reaching

Abstract: Moreau-Debord I, Martin CZ, Landry M, Green AM. Evidence for a reference frame transformation of vestibular signal contributions to voluntary reaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 72 publications
6
28
0
Order By: Relevance
“…Moreau‐Debord et al . () demonstrated that, exactly as for the postural system, the effect of GVS upon arm movement is systematically modulated by head orientation, with the largest effect being observed with the head pitched downward. In this case, the stimulus evokes a sense of yaw motion, resulting in a compensatory leftward (or rightward) arm movement.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…Moreau‐Debord et al . () demonstrated that, exactly as for the postural system, the effect of GVS upon arm movement is systematically modulated by head orientation, with the largest effect being observed with the head pitched downward. In this case, the stimulus evokes a sense of yaw motion, resulting in a compensatory leftward (or rightward) arm movement.…”
Section: Introductionmentioning
confidence: 82%
“…As shown here, the direction of the evoked arm movement is consistently towards the anode electrode, with the largest magnitude observed during head‐down tilt, being minimal when the head is upright (Moreau‐Debord et al . ). This dependence on head orientation is consistent with GVS producing a sensation of head roll about a naso‐occipital axis in the direction of the cathode electrode (Fitzpatrick et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations